2022
DOI: 10.1111/jorc.12423
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a resistance training programme for patients on short daily haemodialysis: A feasibility study

Abstract: Background Kidney failure patients receiving haemodialysis experience protein‐energy wasting, muscle mass loss and physical function impairment. Intradialytic exercise interventions seem to modify these features, but they are often not implemented as a clinical routine. Objective To investigate the feasibility of implementing a supervised intradialytic resistance training programme as a clinical routine for patients receiving short daily haemodialysis. Design A prospective longitudinal study. Participants Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Supervised training programmes may be a sufficient intervention to elevate the level of physical activity in people on dialysis (Wilkinson et al, 2020), as they spend many hours in the centres where their HD is performed. A recent feasibility study suggested resistance training as and intervention with a high long‐term adherence (Ribeiro et al, 2022). However, others may not wish to perform exercises in the nephrology centre if their travel distance is long or the time schedule does not fit into their personal life (Fang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Supervised training programmes may be a sufficient intervention to elevate the level of physical activity in people on dialysis (Wilkinson et al, 2020), as they spend many hours in the centres where their HD is performed. A recent feasibility study suggested resistance training as and intervention with a high long‐term adherence (Ribeiro et al, 2022). However, others may not wish to perform exercises in the nephrology centre if their travel distance is long or the time schedule does not fit into their personal life (Fang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the intradialytic resistance training program may be consulted elsewhere ( Ribeiro et al, 2022c ). In brief, patients underwent two resistance training sessions per week.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the total training load for each intradialytic resistance training session was calculated as the number of sets x number of repetitions x total weight (sum of dumbbell and ankle weights) ( Borresen and Lambert, 2009 ). Finally, the exercise session was interrupted in case of intradialytic complications such as hypotension and hypoglycemia (for more information, check Ribeiro et al, 2022c ).…”
Section: Methodsmentioning
confidence: 99%